2021
DOI: 10.3390/ijerph18010327
|View full text |Cite
|
Sign up to set email alerts
|

Have Policies Tackled Gender Inequalities in Health? A Scoping Review

Abstract: Gender is recognized as one of the most relevant determinants of health inequalities. This scoping review sought to identify and analyse policies, either implemented or formulated as proposals, which aimed to reduce gender inequalities in health. We searched Medline, Web of Science, and Scielo. Of 2895 records, 91 full text articles were analysed, and 33 papers were included. Of these papers, 22 described the process of formulation, implementation, or evaluation of policies whose aim was to reduce gender inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 50 publications
4
24
0
3
Order By: Relevance
“… 8 In the same line, after the Beijing Declaration and Platform for Action's demand for greater attention to the social determinants of health —including gender and multisector programming— and more recently, the 2030 Agenda for Sustainable Development, few policies have been formulated, implemented, or evaluated to tackle gender inequities in health. 9 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 8 In the same line, after the Beijing Declaration and Platform for Action's demand for greater attention to the social determinants of health —including gender and multisector programming— and more recently, the 2030 Agenda for Sustainable Development, few policies have been formulated, implemented, or evaluated to tackle gender inequities in health. 9 …”
mentioning
confidence: 99%
“…Although the overall picture is of slow and unequal progress and the number of studies showing significant improvements seems modest, studies included in different reviews reported progress 7 , 8 , 9 , 13 . It is worth noting that the actions regarding gender bias in healthcare, gender-sensitivity educational interventions, and health and non-health policies aimed at the reduction of gender inequities in health, were successful.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Policy processes that engage women, gender experts, and groups that are marginalised due to identities, such as disability, gender identity, ethnicity, and sexuality, are essential to the development of gender responsive and inclusive health responses. 19,20 However, decision making in relation to national COVID-19 responses has largely adopted an exclusionary, male-dominated approach: a UN Development Programme review found that only 24% of national COVID-19 task force members globally are women. 21 Pandemic responses that do not recognise the importance of sex and gender will always be less equitable and less effective.…”
mentioning
confidence: 99%
“…The absence of health and social resources leaves women at a clear risk of contracting HIV in their search for basic survival resources for themselves and their children. Advancing care and assistance to female victims of disasters will only be possible through approaches that advocate for equality between women and men in terms of access to and fair distribution of opportunities, rights, obligations, and resources [ 91 ]. This research shows that Haitian women had an increase in seropositivity not due to chance and that when their family depended on them, the risk was even greater: the earthquake and HIV are not gender-neutral.…”
Section: Discussionmentioning
confidence: 99%